Nitrogen dynamics of various green manure species and the relationship to lowland rice production - Clément, Alain; Ladha, Jagdish K.; Chalifour, François-P. (Wiley, 1998)
Green manure (GM) is an alternative to mineral fertilizers, particularly for subsistence farmers whose resource base is small. Published information on the influence of the chemical composition of GM on N dynamics in lowland rice (Oryza sativa L.) is scarce. A field experiment was conducted in the 1992 wet season (WS), the 1993 dry season (DS) and the 1993 wet season to compare GM species and urea as sources of N for rice, to monitor N release and uptake during the season, and to verify the effect of the chemical composition of GM on rice yield (including the residual effect on dry season rice). Ten species were compared, with two controls (with and without deep‐placed urea supergranules). Nitrogen from urea or GM crops was applied at the rate of 80 kg N ha−1. Most GM species performed as well as urea supergranules. Cowpea [Vigna unguiculata (L.) Walp.], soybean [Glycine max (L.) Merr.], and sorghum [Sorghum bicolor (L.) Moench] outyielded the urea control in the 1992 wet season. Residual effects of GM incorporation on rice grain yield during the 1993 dry season were generally modest. Rice grain yield response to GM application was comparable for both the 1992 and 1993 wet seasons (r2 = 0.83**). In microplots without rice plants, there was limited GM‐N mineralization past 30 days after transplanting (DAT). Soil NH+4‐N with rice increased until about 20 DAT, and then decreased sharply, because of rice N uptake. At 50 DAT, soil NH+4‐N reached very low levels in all treatments. Rice N uptake between 31 and 52 DAT was explained by the size of early‐season soil NH+4‐N pool (r2 = 0.83**). Higher N uptake rates by rice with GM than with urea from 52 to 69 DAT indicate a better synchrony between GM‐N availability and rice N uptake. The C/N ratio of GM species influenced rice N uptake, but only early in the season.